Transformation of Darussalam Islamic Boarding School in Garut (1986–2021): Institutional, Educational, and Social Aspects - Akbar Rahman Hakim; Ajid Thohir; Fathia Lestari (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study examines the transformation of Pondok Pesantren Darussalam Kersamanah, Garut, from 1986 to 2021 as a dynamic process of institutional adaptation within contemporary Islamic education in Indonesia. This study addresses an important gap in pesantren studies, as previous research has largely focused on general modernization trends, while limited attention has been given to longitudinal historical analyses of pesantren transformation using institutional perspectives. This research employs a historical method involving heuristics, source criticism, interpretation, and historiography. Data were collected from archival documents, institutional records, internal publications, and interviews with key informants. Talcott Parsons’ structural-functional theory was employed as the analytical framework to examine how pesantren adapt to changing social and educational environments while maintaining institutional continuity. The findings reveal that the transformation of Pondok Pesantren Darussalam occurred through three major phases: the pioneering phase (1986–1995), the consolidation phase (1996–2008), and the expansion phase (2009–2021). The transformation involved three major dimensions: institutional transformation, educational transformation, and social transformation. The findings show that Darussalam successfully evolved from a relatively small pesantren into a modern Islamic educational institution through governance restructuring, educational innovation, infrastructure expansion, digital adaptation, and economic strengthening. Despite significant modernization, the pesantren maintained its core identity through the preservation of Islamic values, discipline, classical Islamic scholarship, and character formation. This study demonstrates that pesantren transformation in contemporary Indonesia should be understood as a multidimensional process involving adaptation, continuity, modernization, and institutional sustainability. The study contributes to broader discussions on pesantren studies and Islamic education by offering a structural-functional perspective for understanding the transformation of Islamic educational institutions in modern Indonesia.